A Modified Femtosecond Laser Technique for Anterior Capsule Contraction Syndrome - Marco Marenco; Pietro Mangiantini; Luca Scuderi; Alessandro Lambiase; Marta Sacchetti (Journal of Ophthalmology)
Anterior capsule contraction syndrome (ACCS) is a rare, late complication of cataract surgery, associated with impairment of visual function. In this paper, we describe a new surgical technique to treat ACCS by femtosecond laser procedure. The femtosecond laser was used to perform an anterior capsulotomy with a customized size, in order to avoid IOL damage. After ophthalmic viscosurgical device injection in the anterior chamber, the anterior capsule flap was separated from the IOL surface by gentle hydrodissection. This manoeuvre enabled an easy and safe removal of the fibrotic material by vitreal microscissors. Our technique allowed a complete removal of the fibrotic material and opening of the capsule, with immediate complete visual acuity recovery without IOL damage. In conclusion, femtosecond laser appears to be safe and effective for treatment of ACCS with long-lasting efficacy.